Association between HIV and acquisition of rifamycin resistance with first-line TB treatment: a systematic review and meta-analysis - Nesbert Zinyakatira; Nathan Ford; Helen Cox (BMC Infectious Diseases, 2024)
Abstract Background Multi-drug or rifamycin-resistant tuberculosis (MDR/RR-TB) is an important public health concern, including in settings with high HIV prevalence. TB drug resistance can be directly transmitted or arise through resistance acquisition during first-line TB treatment. Limited evidence suggests that people living with HIV (PLHIV) might have an increased risk of acquired rifamycin-resistance (ARR). Methods To assess HIV as a risk factor for ARR during first-line TB treatment, a systematic review and meta-analysis was conducted. ARR was defined as rifamycin-susceptibility at treatment start with rifamycin-resistance diagnosed during or at the end of treatment, or at recurrence. PubMed/MEDLINE, CINAHL, Cochrane Library, and Google Scholar databases were searched from inception to 23 May 2024 for articles in English; conference abstracts were also searched from 2004 to 2021. The Mantel-Haenszel random-effects model was used to estimate the pooled odds ratio of any association between HIV and ARR among individuals receiving first-line TB treatment. Results Ten studies that included data collected between 1990 and 2014 were identified: five from the United States, two from South Africa and one each from Uganda, India and Moldova. A total of 97,564 individuals were included across all studies, with 13,359 (13.7%) PLHIV. Overall, 312 (0.32%) acquired rifamycin-resistance, among whom 115 (36.9%) were PLHIV. The weighted odds of ARR were 4.57 (95% CI, 2.01–10.42) times higher among PLHIV compared to HIV-negative individuals receiving first-line TB treatment. Conclusion The available data, suggest that PLHIV have an increased ARR risk during first-line TB treatment. Further research is needed to clarify specific risk factors, including advanced HIV disease and TB disease severity. Given the introduction of shorter, 4-month rifamycin-based regimens, there is an urgent need for additional data on ARR, particularly for PLHIV. Systematic review registration PROSPERO CRD42022327337.